Proposed high school science courses for general education - Hernandez, Dolores F. 1924- (1956)
An integrated science program, so organized that it will lend itself with greater facility to the accomplishment of the aims of the General Education, is presented in this study. It is shown in this paper how the natural science courses in the UP Preparatory High School contribute to the general education of the student.
Bibliography: l. 324-333.
Thesis (M.Ed.)--University of the Philippines, 1956
Typewritten
Vita
Keywords: Science -- Study and teaching